Patterns of Outcome-Based Learning Quality Assurance on Competency Demands in the World of Work - Muhammad Noor Fitriyanto (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2021)
The speed of the use of technology and the production of innovation is growing rapidly, creating a gap between the world of education and the human resource needs of the world of work and society. The challenge of 21st century education is to bridge the gap between the educational process in higher education and the innovation of the world of work. One approach used to accommodate 21st century education is quality outcome-based learning. Guaranteeing the quality of education is the obligation of every educational unit and is the right of every element of society. Quality tertiary institutions are those that can provide certainty that all components including organization, policies, and related processes in the education unit can run according to the standards set. The purpose of the discussion of this paper is to photograph and find out the pattern of quality assurance of learning in higher education based on the outcomes of current and future competencies in the world of work. The method used is the meta-analysis study method. The results of the synthesis show that in order to achieve outcome-based quality assurance, all academics involved in the education process up to the employees must understand the nature and purpose of providing education. Good quality in the learning process makes learning innovative, interactive, and effective. Outcomes of quality assurance of knowledge-based learning and skills must really be measurable (concretely measurable) so that they can meet the demands of the competence of the world of work.Keywords: World of Work, Competence, Quality Assurance DOI: http://dx.doi.org/10.23960/jpvti.v3.i2.202105